2010
DOI: 10.1002/jmv.21666
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the geographical origin of unidentified cadavers based on geographical differences in genotype of varicella–zoster virus

Abstract: A new method was developed for determining the geographical origin of unidentified cadavers by examining the genome of varicella-zoster virus (VZV), which resides latently throughout life in most individuals and the genotypes which show distinct geographical distribution. VZV DNA samples extracted from the trigeminal ganglia of 62 cadavers (59 from Japan, and 1 each from the United Kingdom, Mongolia, and Pakistan) submitted for medico-legal autopsy were examined. Sequencing was performed on a 358-bp region in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Our results showed that the VZV strains isolated from patients in suburban Shanghai were primarily genotype J/clade 2 strains, suggesting that the distribution of VZV in China has significant geographical features. The results of our study, combined with those from studies in Japan (Inoue et al, 2010), Korea (Kim et al, 2011) and Mongolia (Enskhsaȋkhan et al, 2010), indicate that the majority of WT VZV strains in north-east Asia are genotype J/clade 2 strains. However, a small fraction of type M2 isolates were identified according to the 447 bp method in our study.…”
Section: Discussionmentioning
confidence: 53%
“…Our results showed that the VZV strains isolated from patients in suburban Shanghai were primarily genotype J/clade 2 strains, suggesting that the distribution of VZV in China has significant geographical features. The results of our study, combined with those from studies in Japan (Inoue et al, 2010), Korea (Kim et al, 2011) and Mongolia (Enskhsaȋkhan et al, 2010), indicate that the majority of WT VZV strains in north-east Asia are genotype J/clade 2 strains. However, a small fraction of type M2 isolates were identified according to the 447 bp method in our study.…”
Section: Discussionmentioning
confidence: 53%
“…Based on the close relationship between genotypic polymorphisms and geographic distributions of HSV‐1 and VZV [Umene et al, 2003; Loparev et al, 2004], the geographic origins of unidentified cadavers may be determined [Inoue et al, 2010b]. However, since only a limited amount of DNA can be extracted directly from the trigeminal ganglia, it is difficult to compare the genotypes of viruses isolated from the right and left ganglia or to determine co‐infection in an ipsilateral ganglion.…”
Section: Introductionmentioning
confidence: 99%
“…One of these methods estimates the geographical origin of a cadaver based on geographical difference in DNA polymorphisms of viruses that reside in humans latently and continuously over the long term. To date, estimation methods of geographical origin based on DNA polymorphisms have been developed for the JC , BK , Epstein‐Barr , and varicella‐zoster viruses. These viruses infect infants and children and establish lifelong latent infection.…”
mentioning
confidence: 99%
“…To date, estimation methods of geographical origin based on DNA polymorphisms have been developed for the JC (3), BK (4), Epstein-Barr (5), and varicella-zoster (6) viruses. These viruses infect infants and children and establish lifelong latent infection.…”
mentioning
confidence: 99%